Premalignant lesions and early cancer of the cervix microinvasive carcinoma: radiotherapy - Pinillo Ashton, Luis (2015)
Cancer of the cervix is capable of being detected by cytology, which is critical because it allows the detection of the disease in early stays and even premalignant phase which affects a high percentage of cures, cures that are real and not just a temporary freeze tumor. It is important to change attitudes to cancer and should disseminate the fact that cancer is curable. The micro-invasive cancer is the treatment of choice in our institution radical hysterectomy without lymphadenectomy for reasons of better diagnosis and preservation of ovarian function but radiation therapy as Radium uterovaginal application has its indications and radiobiological base and results in cure as good as surgery that support them.